Advances in integration of photovoltaic power and energy production in practical systems - Fartaria, Tomás de Oliveira (2017)
This thesis presents advances in integration of photovoltaic (PV) power and energy in practical systems, such as existing power plants in buildings or directly integrated in the public electrical grid. It starts by providing an analyze of the current state of PV power and some of its limitations. The work done in this thesis begins by providing a model to compute mutual shading in large PV plants, and after provides a study of the integration of a PV plant in a biogas power plant. The remainder sections focus on the work done for project PVCROPS, which consisted on the construction and operation of two prototypes composed of a PV system and a novel battery connected to a building and to the public electrical grid. These prototypes were then used to test energy management strategies and validate the suitability of the two advanced batteries (a lithium-ion battery and a vanadium redox ow battery) for households (BIPV) and PV plants. This thesis is divided in 7 chapters: Chapter 1 provides an introduction to explain and develop the main research questions studied for this thesis; Chapter 2 presents the development of a ray-tracing model to compute shading in large PV elds (with or without trackers); Chapter 3 shows the simulation of hybridizing a biogas plant with a PV plant, using biogas as energy storage; Chapters 4 and 5 present the construction, programming, and initial operation of both prototypes (Chapter 4), EMS testing oriented to BIPV systems (Chapter 5). Finally, Chapters 6 provides some future lines of investigation that can follow this thesis, and Chapter 7 shows a synopsis of the main conclusions of this work; Resumo: Avanços na integracão de potência fotovoltaica e producão de energia em sistemas práticos Esta tese apresenta avanços na integração de potência e energia fotovoltaica (PV) em sistemas práticos, tais como centrais existentes ou a rede eléctrica pública. Come ça por analisar o estado corrente do fotovoltaico no mundo e aborda algumas das suas limitações. O trabalho feito para esta tese de doutoramento começou pelo desenvolvimento de um modelo para calcular os sombreamentos que ocorrem em grandes campos fotovoltaicos, e depois apresenta um estudo sobre a integração um sistema fotovoltaico em uma central eléctrica a bióg as. As ultimas secções da tese focam-se no trabalho feito para o projecto PVCROPS, que consistiu na construção e operação de dois demonstratores, cada um formado por um sistema fotovoltaico e bateria conectados a um edíficio e a rede eléctrica pública. Estes protótipos foram posteriormente utilizados para testar estratégias de gestão de energia (EMS) e para validar a operação de duas baterias avançadas (bateria de Iões de Li tio e bateria de Fluxo Redox de Van adio) e a sua utiliza ção para habitações e centrais PV. A tese está dividida em 7 capitulos: O capitulo 1 apresenta uma introdução para explicar e desenvolver as principais questões que foram investigadas nesta tese; O capitulo 2 mostra o desenvolvimento de um modelo baseado em traçados de raios para calcular sombreamentos mútuos em grandes centrais PV (com e sem seguidores); O capitulo 3 mostra a simulação da hibridização de uma central electrica a biogas com uma central PV, e utilizando o biógas como armazenamento de energia. Os capitulos 4 e 5 apresentam a construção, programação e operação inicial dos dois demonstradores (Capitúlo 4), o teste de EMS orientadas para sistemas PV em habitações (Capítulo 5). Finalmente, o capítulo 6 sugere algumas futuras linhas de investigação que poderão seguir esta tese, e o Capítulo 7 faz uma sinopse das principais conclusões deste trabalho.